Split-agar assay of antifungal soil microbial metabolites. (April 2016) - Aparna, K.; Rao, D.L.N.
Abstract: Soil microorganisms suppress soil borne plant pathogenic fungi through various mechanisms. There is no appropriate, integrated method to easily quantify soil health in terms of disease control ability. A novel assay to quantify the ability of soil to inhibit fungal pathogens is described. The technique is easy to use routinely in soil biology investigations for soil quality testing as it offers an integrated expression of suppressiveness as actidione equivalents per gram of soil. Soil samples were inoculated into liquid growth medium and incubated; supernatants were filter sterilized and assayed in split agar against Macrophomina phaseolina to record colony radius. The antifungal activity of the soils varied widely ranging from 0.02 to 2.80 mg actidione equivalents g −1 soil, of which 81–98% was heat labile. The test will be a useful aid in decision support for reducing the use of chemical control agents and promote sustainable farming practices.